Otomatisasi Pemantauan dan Penyiraman Lidah Mertua dengan Sensor LDR dan Kelembaban Tanah - Nanda Aprilia Damayanti; Abdurrakhman Hamid Al-Azhari; Djuniadi Djuniadi (Lembaga Penelitian Universitas Balikpapan, 2024)
Abstract— Indonesia is a country that has a diversity of flora, one of which is ornamental plants. The types of ornamental plants are very diverse, one of which is the mother-in-law's tongue plant. Each plant has different needs for growth depending on the ornamental plant, starting from the need for water, soil moisture and sunlight. Based on these influencing factors, if it is not suitable, the ornamental plant will die, and this will also happen to the mother-in-law's tongue plant. Therefore, research entitled